The Effect of Managerial Ownership, Profitability, and Company Size on Financial Performance in Basic Materials Companies Listed on the Indonesia Stock Exchange for the Period 2020–2023 - Sari, Widya Permata; Khasanah, Uswatun; Yuniati, Triana (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
This study aims to examine the Influence of Managerial Ownership, Profitability and Company Size on Financial Performance in Basic Materials Companies listed on the Indonesia Stock Exchange for the period 2020 – 2023. The variables used in this study are Financial Performance as a dependent variable, and Managerial Ownership, Profitability and Company Size as independent variables. The sampling technique used was the purposive sampling method and obtained as many as 33 samples of companies from 93 companies listed on the Indonesia Stock Exchange (IDX) and the number of observations was 123 data samples. The data processing in this study uses IBM SPSS (Statistical Product and service solution) version 23. The results of this study show that Managerial Ownership has no effect on Financial Performance, Profitability has a positive effect on Financial Performance, and Company Size has a negative effect on Financial Performance.